2015
DOI: 10.1097/hcm.0000000000000038
|View full text |Cite
|
Sign up to set email alerts
|

A Ministudy of Employee Turnover in US Hospitals

Abstract: A mini-study was conducted to collect self-reported employee turnover rates in U.S.hospitals. The results indicate many hospitals are struggling with high employee turnover rates.Wide-spread variances in ratings were observed across hospitals which may be due to lack of consistency in how they each calculate their employee turnover. This makes benchmarking for the purposes of performance improvement challenging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
(6 reference statements)
0
9
0
Order By: Relevance
“…Health care systems are also uniquely vulnerable to phishing attacks. Employee turnover at hospitals is high, 20 and there is a constant influx of new employees (eg, trainees) who may have no prior cybersecurity training, which creates a continuous stream of newly susceptible employees. Hospital systems are vulnerable due to significant end point complexity, a term used to describe the large number of IT devices that could be targeted in an attack.…”
Section: Discussionmentioning
confidence: 99%
“…Health care systems are also uniquely vulnerable to phishing attacks. Employee turnover at hospitals is high, 20 and there is a constant influx of new employees (eg, trainees) who may have no prior cybersecurity training, which creates a continuous stream of newly susceptible employees. Hospital systems are vulnerable due to significant end point complexity, a term used to describe the large number of IT devices that could be targeted in an attack.…”
Section: Discussionmentioning
confidence: 99%
“…Turnover is how long an employee stays in his or her employment (Currie & Carr Hill, 2011). Employee turnover costs U.S. companies billions annually (Collins, McKinnies, Matthews, & Collins, 2015). There are two types of turnover: voluntary and involuntary.…”
Section: Nursing Turnovermentioning
confidence: 99%
“…Dawson et al, (2014) found higher workloads associated with decreased job satisfaction. High turnover relates to lower employee morale and diminished employee engagement (Collins et al, 2015). For organizations to help increase nursing job satisfaction, strategies included salaries, workload organization, and personal and career development (Buchan, 2013).…”
Section: Job Satisfactionmentioning
confidence: 99%
“…Faculty retention is relatively low, as the 10-year attrition rate of first-time assistant professors is 43 % [14]. Cost estimates for replacing one faculty member can range from $250,000 [15] to $400,000 [16] or from 32 % to 114 % of the annual salary paid to the faculty member leaving [17]. Reduction in turnover can lead to a financial benefit to the AMC.…”
mentioning
confidence: 99%
“…Indirect costs to the AMC related to turnover include loss of patient referrals, reduced teaching and research opportunities, and potentially a negative impact on the reputation of the medical center [16]. Further, high employee turnover is linked to decreased employee morale and productivity [17], which can increase indirect costs to the AMC.…”
mentioning
confidence: 99%